CONDITIONS OF TRANSACTION VALIDITY UNDER RUSSIAN AND FRENCH LAW - E. V. Vershinina,; J. A. Stakheeva (Vestnik MGIMO-Universiteta)
In the article the authors give the main characteristics of conditions of transaction validity according to the Russian and French law. In Russia, as well as in France, a transaction (agreement) which does not meet any of these conditions may be recognized as invalid in part or in full. The conditions of transaction validity are not specified directly in Russian laws, in contrast to the French legislation. Russian lawyers share the opinion that the conditions of transaction validity include the following: the content and the legal result of the transaction must not contradict to law; individuals and legal entities performing the transaction, must have capacity to be a party to the transaction; the expressed will of the transaction party must correspond to its actual will; the will of the transaction party must be expressed in due form. French legislation, in particular, the French Civil Code in the Article 1108 directly specifies the following conditions of transaction (agreement) validity: the party, which undertakes its obligations, must express its consent; the parties must have the capacity to make an agreement; certain subject, which represents the obligation's content; causa of the obligation. Article 1108 of the FCC does not contain direct provisions regarding the form of the transaction. However, in order to be valid, the transaction must be executed in certain legally established form. Also the article deals with the main common and different features in Russian and French legislation and doctrine.